Development and initial validation of a damage index (DIAPS) in patients with thrombotic antiphospholipid syndrome (APS). (August 2015) - Amigo, M-C; Goycochea-Robles, M V; Espinosa-Cuervo, G; Medina, G; Barragán-Garfias, J A; Vargas, A; Jara, L Javier
Introduction: In antiphospholipid syndrome (APS), certain principal manifestations are associated with a worse prognosis and organ damage. Objective: The objective of this paper is to describe the development and initial content, criterion and construct validity of a disease-specific cumulative damage index in patients with thrombotic APS (DIAPS). Methods: Through expert panel agreement, 47 items were considered to reflect damage in APS. This preliminary version of the DIAPS was submitted to four local and international clinical and research experts in APS who ranked each item according to severity. A Delphi exercise resulted in a final 37 item instrument. In the second phase, a cross-sectional study was conducted applying the DIAPS in patients included in a multicenter electronic registry of patients with APS. Quality of life related to health status was evaluated with the EuroQol for construct validation. An α Cronbach and correlation with the EuroQol scale were calculated with SPSS 20.0 ( p  < 0.05). Results: We evaluated the DIAPS in 156 patients, 77% female, with a mean age at diagnosis 34.7 ± 5.5 years. A total of 69% had primary APS. Common comorbidities included obesity, depression and dyslipidemia. The most frequent manifestations resulting in sequelae were deep venous thrombosis and ischemic stroke. Blindness, retinal occlusive vessel disease, myocardial infarction, cardiac valve requiring replacement, mesenteric thrombosis, and renal insufficiency also occurred. Homogeneity: α Cronbach 0.619. DIAPS items correlated with EuroQol domains with the exception of pulmonary, renal, gastrointestinal, and endocrine systems. Conclusion: This study demonstrates content, criterion and construct validity of a new physician-reported instrument to assess the DIAPS. In addition, the DIAPS correlated with the EuroQol.